2008
DOI: 10.1371/journal.pone.0003793
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of the PKC Novel Isoforms, PKCδ and PKCε, in Mouse and Human Platelets

Abstract: BackgroundIncreasing evidence suggests that individual isoforms of protein kinase C (PKC) play distinct roles in regulating platelet activation.Methodology/Principal FindingsIn this study, we focus on the role of two novel PKC isoforms, PKCδ and PKCε, in both mouse and human platelets. PKCδ is robustly expressed in human platelets and undergoes transient tyrosine phosphorylation upon stimulation by thrombin or the collagen receptor, GPVI, which becomes sustained in the presence of the pan-PKC inhibitor, Ro 31-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 38 publications
7
67
1
Order By: Relevance
“…However, Pears et al 45 and Buensuceso et al 46 failed to identify PKCε in human platelets. Thus, in order to resolve the issue, we subjected human and murine platelet lysates to Western Blot analysis using custom made antibody against PKCε (Gift from Dr. Messing, Gallo Centre, San Francisco).…”
Section: Discussionmentioning
confidence: 99%
“…However, Pears et al 45 and Buensuceso et al 46 failed to identify PKCε in human platelets. Thus, in order to resolve the issue, we subjected human and murine platelet lysates to Western Blot analysis using custom made antibody against PKCε (Gift from Dr. Messing, Gallo Centre, San Francisco).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the presence of a threonine group at position Y ϩ 1 or Y ϩ 2 is of also of interest given previous observations in mast cells and mouse platelets that phosphorylation of a conserved threonine at position Y ϩ 1 in 1 of the 2 YxxL sequences of the FcR␥-chain by a novel isoform of protein kinase C (␦ or ⑀) is required for maximal binding and activation of Syk. [27][28][29] Based on these alignments, experiments were designed to investigate the role of the YxxL, and the conserved serine and threonine residues in the cytoplasmic tail of CLEC-2 through a combination of peptide pull-down studies using human CLEC-2 For personal use only. on March 28, 2019. by guest www.bloodjournal.org From cytosolic peptides and human mutant CLEC-2 transfected into chicken DT40 B cells.…”
mentioning
confidence: 99%
“…In fact, it is known that in human normal platelets, PKC epsilon is nearly absent (25,26). This kinetic of expression can be altered during malignant megakaryopoiesis, as we showed that PKCepsilon is over-expressed in PMF MKs accounting for enhanced proliferation and impaired differentiation (13,14).…”
Section: Mf Platelets Are Characterized By Higher Levels Of Pkcepsilonmentioning
confidence: 53%